In vitro culture of metroxylon sagu-the sago palm-a preliminary study - Krishnapillay, Baskaran (1986)
The sago palm (Metroxylon sagu) is an under-exploited starch storing tropical crop which has great commercial potential. Excised embryos of this palm were cultured in vitro for the first time. Suitable sterilization methods, media, addenda and cultural conditions for normal development of embryos and for callus production from excised embryos were investigated. As a large number of fruit (1000 - 2000) were collected at each harvest and owing to the recalcitrant nature of the enclosed seeds, a suitable method for storage of the fruit prior to use was also investigated. Storage of fruit in perforated polythene bags in a cold room (4°C) was found to be a suitable method of storage for these fruit. However, the storage period was only two weeks, after which the viability of the excised embryos deteriorated rapidly. 10% Clorox for 25 minutes was found to be a suitable sterilization procedure for the excised embryos. On Tisserat and DeMason's (1980) medium containing either 2.0 - 2.5 mgr 1 NAA and 0.2 mgl⁻¹ BAP or 1.5 mgl⁻¹ 2, 4-D and 0.2 mgl⁻¹ 2iP in the presence of 3 gl⁻¹ activated charcoal normal shoot and root development of excised embryos was obtained when cultures were incubated in the light at 28°C- 29°C. On a similar basal medium containing either 25 mgl⁻¹ NAA or 15 mgl⁻¹ 2, 4-D or 10 mgl⁻¹ 2, 4-D in combination with 1mgl⁻¹ 2iP, in the absence of charcoal, excised embryos began to form callus. Callus formation occurred both in the light and in the dark in these media containing NAA, while in media containing only 2, 4-D or 2, 4-D in combination with 2iP, callus production was promoted in the dark.